Development of a Training Line Selection Procedure with Support for Compact Hypotheses in Characterization (International Journal of Psychosocial Rehabilitation, 2020)
This research paper explores the problem of improving the quality of recognition of objects by creating a selective study of the compact positioning of objects in solving problems of image identification. Image identification was done by refining the algorithm for the nearest neighbors. k is improved by introducing the flexible functionality of an adjacent algorithm. At the same time, the theory proposed by solving practical problems has been verified.